2013
DOI: 10.1073/pnas.1309393110
|View full text |Cite
|
Sign up to set email alerts
|

R-spondin3 prevents mesenteric ischemia/reperfusion-induced tissue damage by tightening endothelium and preventing vascular leakage

Abstract: Inflammation and vascular injury triggered by ischemia/reperfusion (I/R) represent a leading cause of morbidity and mortality in a number of clinical settings. Wnt and its homolog partners R-spondins, in addition to regulating embryonic development have recently been demonstrated to serve as wound-healing agents in inflammation-associated conditions. Here we ask whether R-spondins could prevent inflammation-associated tissue damage in ischemic disorders and thus investigate the role of R-spondin3 (R-spo3) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 33 publications
5
54
0
Order By: Relevance
“…Increasing barrier function has been shown to limit inflammation in models of ischemia-reperfusion injury and several other models of acute injury [40] [41]. Although the RAR is also an acute model of inflammation, increasing barrier function to limit the number of activated neutrophils transmigrating into tissues may have long term consequences on organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing barrier function has been shown to limit inflammation in models of ischemia-reperfusion injury and several other models of acute injury [40] [41]. Although the RAR is also an acute model of inflammation, increasing barrier function to limit the number of activated neutrophils transmigrating into tissues may have long term consequences on organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Kannan et al [80] found that R-spondin3 (R-spo3) can maintain the integrity of endothelial cell barriers by enhancing the junctions between endothelial cells and preserving the positions of VE-cadherin and F-actin in the cellular peripheral zone. It has been confirmed that both inflammation and apoptosis secondary to subarachnoid hemorrhage (SAH) are of significance because of increases in vascular permeability.…”
Section: New Methods For the Prophylaxis And Treatment Of Vascular Lementioning
confidence: 99%
“…Furthermore, the presence of PLPs was visibly seen in the infarct area of heart tissue sections whereas none could be detected for the plain liposomes (Figure C). At 72 h postinfarction, most of the vascular leakages at the heart were likely had been sealed, suggesting the detected PLPs had infiltrated the heart through monocyte‐mediation rather than by EPR effect.…”
Section: Resultsmentioning
confidence: 99%